Intraoperative Fluoroscopic Verification of Satisfactory Foraminotomy in Posterior Open Decompression Surgery for Lumbar Foraminal Stenosis: A Clinical Image - Stylianos Kapetanakis; Joanna Bladowska; Paschalis Tsioulas; Georgios Tsolakidis; Christos Siopis; Nikolaos Gkantsinikoudis (Clinical Case Reports, 2025)
ABSTRACT Lumbar spinal stenosis (LSS) represents an increasingly encountered disorder in current clinical practice, being unfavorably associated with chronic low back pain, progressive neurologic decline and disability. LSS represents the major etiology for spine surgery in elderly individuals. In the era of continuous development of novel full‐endoscopic techniques, conventional open surgery with decompression of neural elements and with or without fusion of the compromised segment continues to represent the current gold standard for surgical management of these patients. In cases with foraminal stenosis, foraminal decompression with mobilization of the exiting nerve root represents the primary aim of surgery. However, intraoperative proper identification of the extent of decompression may be problematic in specific cases with significantly altered anatomy. The aim of this clinical image is to present a rare case of a patient with symptomatic foraminal stenosis, in which the rate of satisfactory foraminal decompression was intraoperatively verified via routine C‐arm fluoroscopy. To our best knowledge, the utilization of fluoroscopy for verification of the extent of decompression in lumbar foraminal stenosis has never been reported in contemporary literature. Therefore, except for routine localization purposes, intraoperative fluoroscopy may be considered an additional measure to assess foraminal decompression in such cases.